The reliability of fine needle aspiration cytology in the diagnosis of thyroid swelling - Syed, Obaid; Auti, Anand (International Surgery Journal, 2017)
Background: For a thyroid swelling, FNAC is the primary investigation. In most of the lesions, after excision, the Histopathology remains the same, but at times a few surprises do occur when FNAC reported benign lesions are found to be malignant on histopathology. The study aims to find reliability of FNAC in diagnosing Thyroid Lesions. Methods: This prospective study was conducted on 111 patients with thyroid swelling attending IIMSR, Medical College, Jalna during a period of two years. These patients with thyroid lesions were subjected to FNAC and then following the surgery correlated with the histopathology report. Results: Majority of the patients were in the age group of 30-50 years with female predominance. Out of 111 patients studied with FNAC, 1 sample was inadequate. Among remaining 110 cases 99 were benign thyroid lesions, 6 were malignant and 5 were highly suspicious of malignancy. HPE of thyroid specimen confirmed 101 cases as benign and 9 cases as malignant. Case in which inadequate material was obtained on FNAC was not included in study. Conclusions: FNAC is about 98.18 % reliable in diagnosing thyroid lesions. FNAC is easy, reliable and accurate investigation for all thyroid swellings.